Characterizing solute hydrogen and hydrides in pure and alloyed titanium at the atomic scale - Chang,Y; Breen,AJ; Tarzimoghadam,Z; Kürnsteiner,P; Gardner,H; Ackerman,A; Radecka,A; Bagot,PAJ; Lu,W; Li,T; Jägle,EA; Herbig,M; et al. (Acta Materialia, 2018)
Ti has a high affinity for hydrogen and are typical hydride formers. Ti-hydride are brittle phases which probably cause premature failure of Ti-alloys. Here, we used atom probe tomography and electron microscopy to investigate the hydrogen distribution in a set of specimens of commercially pure Ti, model and commercial Ti-alloys. Although likely partly introduced during specimen preparation with the focused-ion beam, we show formation of Ti-hydrides along α grain boundaries and α/β phase boundaries in commercial pure Ti and α+β binary model alloys. No hydrides are observed in the αphase in alloys with Al addition or quenched-in Mo supersaturation.